STUDI FISIBILITAS SISTEM JARINGAN DISTRIBUSI AIR BERSIH DI DESA SUNGSANG KABUPATEN BANYUASIN - Mukhlis Mukhlis; Hamdi Hamdi (PILAR, 2012)
Sungsang Village placed in Musi River downstream, littoral terrain of Sumatra Island. Nevertheless, its inhabitant has difficulty in acquiring sanitary water. Existent water resources are still hampered by limited quantity and quality, as well as the costly price. Water Treatment Plant (WTP) at Sungsang Village which was provided by the authorities -applying ultrafiltration and reverse osmosis technology- could not be functioned since 2007 considering that operational funding inadequacies and unavailability of the water distribution systematization. This research aims to analyze feasibility on water distribution network system at Sungsang Village wchich is focused on the amount of investation needed. The analysis method in this study includes to observe the water needs aspects by conducting the water utilization survey at the household stratum, then to analyze technical aspect and finally to analyze the engineering economic aspects. There are two configuration alternative models, which are technically calculated and simulated using computer program. Subsequently, the whole of investments is evaluated in financial feasibility with certain criteria that have been determined. This research concudes that alternative I is more feasible than that of alterntive II.